Lexicon Discovery for Language Preservation using Unsupervised Word Segmentation with Pitman-Yor Language Models (FGNT-2015-01) - Walter, Oliver; Haeb-Umbach, Reinhold; Strunk, Jan; P. Himmelmann, Nikolaus
In this paper we show that recently developed algorithms for unsupervised word segmentation can be a valuable tool for the documentation of endangered languages. We applied an unsupervised word segmentation algorithm based on a nested Pitman-Yor language model to two austronesian languages, Wooi and Waima'a. The algorithm was then modified and parameterized to cater the needs of linguists for high precision of lexical discovery: We obtained a lexicon precision of of 69.2% and 67.5% for Wooi and Waima'a, respectively, if single-letter words and words found less than three times were discarded. A comparison with an English word segmentation task showed comparable performance, verifying that the assumptions underlying the Pitman-Yor language model, the universality of Zipf's law and the power of n-gram structures, do also hold for languages as exotic as Wooi and Waima'a.

Making cars a main ICT resource in smart cities - Altintas, Onur; Dressler, Falko; Hagenauer, Florian; Matsumoto, Makiko; Sepulcre, Miguel; Sommer, Christoph (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Timings Matter - Bloessl, Bastian; Puschmann, Andre; Sommer, Christoph; Dressler, Falko (ACM SIGMOBILE Mobile Computing and Communications Review)

Power matters: Automatic Gain Control for a Software Defined Radio IEEE 802.11a/g/p receiver - Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (2015 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

The scrambler attack: A robust physical layer attack on location privacy in vehicular networks - Bloessl, Bastian; Sommer, Christoph; Dressier, Falko; Eckhoff, David (2015 International Conference on Computing, Networking and Communications (ICNC))

Simulative performance evaluation of vehicular networks - Eckhoff, David; Sommer, Christoph (Vehicular Communications and Networks)

Poster: A simulator for heterogeneous vehicular networks - Hagenauer, Florian; Dressler, Falko; Sommer, Christoph (2014 IEEE Vehicular Networking Conference (VNC))

Fairness kills safety: A comparative study for intersection assistance applications - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Dressler, Falko (2014 IEEE 25th Annual International Symposium on Personal, Indoor, and Mobile Radio Communication (PIMRC))

Enabling Situation Awareness at Intersections for IVC Congestion Control Mechanisms - Joerer, Stefan; Bloessl, Bastian; Segata, Michele; Sommer, Christoph; Cigno, Renato Lo; Jamalipour, Abbas; Dressler, Falko (IEEE Transactions on Mobile Computing)

MCB – A multi-channel beaconing protocol - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (Ad Hoc Networks)